2017
DOI: 10.3390/en10091250
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Idle-Stop-Start Control of Micro Hybrid Construction Equipment—Part B: A Real-Time Comparative Study

Abstract: Micro hybrid propulsion (MHP) technologies have emerged as promising solutions for minimisation of fuel consumption and pollutant emissions of off-highway construction machines (OHCMs). Their performance and economic feasibility strongly depend on the way they utilize the idle-stop-start control (ISSC) concept. The ISSC design process and performance evaluation are particularly challenging due to the peculiar structures and dynamics of OHCMs compared to other vehicles and, therefore, require significant develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…These so called implements must receive power from a power take off (PTO) connection to work properly because they are usually not equipped with an autonomous power source. Several studies in the literature showed the possibility of performance optimization in working vehicles through proper energy management strategies [22][23][24]. However, it must be noted that these techniques are specifically designed for the tasks associated with the specific type of machine.…”
Section: Introductionmentioning
confidence: 99%
“…These so called implements must receive power from a power take off (PTO) connection to work properly because they are usually not equipped with an autonomous power source. Several studies in the literature showed the possibility of performance optimization in working vehicles through proper energy management strategies [22][23][24]. However, it must be noted that these techniques are specifically designed for the tasks associated with the specific type of machine.…”
Section: Introductionmentioning
confidence: 99%